Enabling knowledge transfer between IS and business personnel - Singh, Gurmak (2004)
Knowledge transfer between IS and business personnel has been identified as an important precursor to innovation. Studies in IS have strongly recommended that IS and business managers cooperate more closely to foster knowledge transfer.These studies urge senior management to search for new ways to promote co-operation between IS and business managers to enhance the value they create.However, the literature of information systems suggests that substantial discord exists between IS and business groups resulting in erection of barriers to knowledge management.The relationship has traditionally been poor, a problem characterised by a lack of mutual understanding and trust.This paper explores the conditions necessary for cooperative relationships between IS and business managers that will foster knowledge transfer.Factors involved in the dissolution of knowledge transfer are also explored.The paper also provides recommendations for senior managers in fostering knowledge transfer environments.